Hydro-graph: A knowledge graph for hydrogen research trends and relations. (7th August 2020) - Lin, Rongheng; Fang, Qiyu; Wu, Budan
Abstract: The field of hydrogen research is a huge community, generating a large amount of literature every year. Researchers need to do a lot of review to get a general understanding of the field, and to realize the research trends and relations. Since the reviews are done manually by the researchers, it is not only inefficient but the timing of the reviews might not be real time. This paper presents a tool called Hydro-graph, which aims to provide researchers in the field of hydrogen research with a knowledge graph of relevant fields. It can help researchers quickly understand the development status, research hotspots and research trends of a certain field. Furthermore, it can find representative authors in the field, and analyse their research direction and development process. Experimental results show that Hydro-graph can effectively help researchers in the hydrogen research community to analyse relevant fields.